Matrix structural analysis - Felton, Lewis P.; Nelson, Richard B. (New Delhi Wiley India, 1997)
A rigorous, concise development of the concepts of modern matrix structural analysis, with particular emphasis on the techniques and methods that form the basis of the finite element method. All relevant concepts are presented in the context of two-dimensional (planar) structures composed of bar (truss) and beam (frame) elements, together with simple discrete axial, shear and moment resisting spring elements. The book requires only some basic knowledge of matrix algebra and fundamentals of strength of materials.
Keywords: Civil Engineering